2019
DOI: 10.5194/acp-19-1491-2019
|View full text |Cite
|
Sign up to set email alerts
|

Viscosities, diffusion coefficients, and mixing times of intrinsic fluorescent organic molecules in brown limonene secondary organic aerosol and tests of the Stokes–Einstein equation

Abstract: Abstract. Viscosities and diffusion rates of organics within secondary organic aerosol (SOA) remain uncertain. Using the bead-mobility technique, we measured viscosities as a function of water activity (aw) of SOA generated by the ozonolysis of limonene followed by browning by exposure to NH3 (referred to as brown limonene SOA or brown LSOA). These measurements together with viscosity measurements reported in the literature show that the viscosity of brown LSOA increases by 3–5 orders of magnitude as the aw de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 89 publications
(122 reference statements)
5
27
0
1
Order By: Relevance
“…Diffusion coefficients in brown limonene SOA are reported as a function of aw in Ullmann et al (2019). The viscosity of brown limonene SOA matrices as a function of aw were also reported in that work.…”
Section: S22 Matrices Consisting Of Brown Limonene Soa Generated In supporting
confidence: 56%
See 1 more Smart Citation
“…Diffusion coefficients in brown limonene SOA are reported as a function of aw in Ullmann et al (2019). The viscosity of brown limonene SOA matrices as a function of aw were also reported in that work.…”
Section: S22 Matrices Consisting Of Brown Limonene Soa Generated In supporting
confidence: 56%
“…Organic Molecule Radius (Å) Reference Diffusing Fluorescein 5.02 (Mustafa et al, 1993) Rhodamine 6G 5.89 (Müller and Loman, 2008) Calcein 7.4 (Tamba et al, 2010) Cresyl violet 3.7 Molecular radius calculated using Van der Waals theory of atomic increments (Edward, 1970) Diffusing and matrix Sucrose 4.5 Based on the density of amorphous sucrose (Chenyakin et al, 2017) Brown limonene SOA components 5.4 ± 0.9 (Ullmann et al, 2019) Matrix Citric acid 3.7 (Müller and Stokes, 1956) Sorbitol 3.6 (Comper, 1996)…”
Section: Diffusing or Matrix Speciesmentioning
confidence: 99%
“…One physicochemical property of SOA that remains insufficiently understood is liquid-liquid phase separation (LLPS) (Pankow, 2003;Marcolli and Krieger, 2006;Ciobanu et al, 2009;Bertram et al, 2011;Krieger et al, 2012;Song et al, 2012a;Zuend and Seinfeld, 2012;Veghte et al, 2013;You et al, 2014;O'Brien et al, 2015;Freedman, 2017). Very recent work has shown that SOA particles free of inorganic salts can undergo LLPS at a high relative humidity (RH) with implications for predicting the cloud nucleating properties of SOA (Petters et al, 2006;Hodas et al, 2016;Renbaum-Wolff et al, 2016;Ovadnevaite et al, 2017;Rastak et al, 2017;Song et al, 2017Song et al, , 2018Altaft et al, 2018;Liu et al, 2018;Davies et al, 2019;Ham et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The effective diffusion coefficient for IEPOX through the organic coating (Dorg) was then calculated using the Stokes-Einstein Equation (refer to Eq. (1)), assuming that = 1 nm (Evoy et al, 2019;Ullmann et al, 2019). = 0 .…”
Section: Phase State and Its Impact On Reactive Uptake: Overviewmentioning
confidence: 99%
“…When aerosols form a core-shell morphology, experimentally observed viscosities of the outer organic-rich shell and inner electrolyte-rich core have been shown to differ by up to three orders of magnitude resulting in possible diffusion limitations on reactive uptake (Ullmann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%